Femicide, criminology and the law - Dayan, Hava; Bitton, Yifat (Abingdon, Oxon ; New York, NY : Routledge, 2023)
This book offers an interdisciplinary perspective on femicide, using Israel as an illuminating case study, given its diverse communities and common-law-based legal system. Utilizing analytical alongside practical perspectives, the book offers a novel crimino-legal approach to femicide. In addition to its interdisciplinary novelty, the book presents originality in going beyond the more usual focus on the central victims and the common legal tools. Here, the authors extend the analysis to secondary victims of femicide and examine the applicability of second-tiered relevant legal tools, mostly tort law, as a means for gaining justice for the victims. This explorative journey culminates with the authors' definition of femicide as a quintessential "crime of distinct nature". In the context of current international pledges to better understand and consequently better fight femicide, this work allows readers to comprehend the phenomenon and the ways to abolish it. The book will be an invaluable resource for academics, researchers and policy makers working in the areas of criminal law, tort law, family law, criminology and gender studies, as well as for legal theorists and criminologists seeking integration of both disciplines.
OCLC-licensed vendor bibliographic record.
Keywords: Women -- Crimes against -- Israel; Homicide -- Law and legislation -- Israel; Feminist jurisprudence -- Israel; LAW / Criminal Law / General; SOCIAL SCIENCE / Criminology